2018
DOI: 10.1074/jbc.m117.807180
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and cell-derived extracellular vesicles protect hippocampal neurons from oxidative stress and synapse damage induced by amyloid-β oligomers

Abstract: Alzheimer's disease (AD) is a disabling and highly prevalent neurodegenerative condition, for which there are no effective therapies. Soluble oligomers of the amyloid-β peptide (AβOs) are thought to be proximal neurotoxins involved in early neuronal oxidative stress and synapse damage, ultimately leading to neurodegeneration and memory impairment in AD. The aim of the current study was to evaluate the neuroprotective potential of mesenchymal stem cells (MSCs) against the deleterious impact of AβOs on hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
127
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 92 publications
7
127
1
Order By: Relevance
“…We also found that hUC-MSCs could reduce oxidative stress in the brains of AD mice. Some researchers demonstrated that extracellular vesicles secreted by MSCs (MSC-MVs) carried endogenous antioxidant enzymes (e.g., catalase) that endowed ROS scavenging activity (de Godoy et al, 2018). MSC-MVs were able to prevent the expression of PTGS2 transcripts and reduce iNOS enzymes and NO injury (Jaimes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that hUC-MSCs could reduce oxidative stress in the brains of AD mice. Some researchers demonstrated that extracellular vesicles secreted by MSCs (MSC-MVs) carried endogenous antioxidant enzymes (e.g., catalase) that endowed ROS scavenging activity (de Godoy et al, 2018). MSC-MVs were able to prevent the expression of PTGS2 transcripts and reduce iNOS enzymes and NO injury (Jaimes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be taken into account a possible indirect role of neurons or other glial cells in modifying the expression of the phagocytic marker in vivo; something that cannot be guaranteed in our experimental model in vitro. Remarkably, a direct effect of MSC‐EVs has been described in primary hippocampal cultures that turned out to be protected from oxidative stress and synapse damage induced by amyloid‐β oligomers 102,103 . However, our experiments on 3xTg hippocampal neurons (Figure S6) seem to rule out, at least in our experimental settings, a direct effect on neuronal activity.…”
Section: Discussioncontrasting
confidence: 46%
“…Likewise, upregulation of CAT associates with the antioxidant properties of MSCs in aging and colitis which parallels measurable reductions in H 2 O 2. 33,34 Exosomes derived from MSCs also express functional CAT 31,83 . Inhibition of CAT suppresses their protective effects on amyloid‐β oligomer‐induced damage to hippocampal neurons indicating that this enzyme may also mediate antioxidant effects of MSCs 83 .…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 99%
“… 33,34 Exosomes derived from MSCs also express functional CAT 31,83 . Inhibition of CAT suppresses their protective effects on amyloid‐β oligomer‐induced damage to hippocampal neurons indicating that this enzyme may also mediate antioxidant effects of MSCs 83 . MSC treatments have also been demonstrated to upregulate the expression of GPx in septic lung injury, severe acute pancreatitis, small bowel ischemia/reperfusion (I/R) injury, and Friedreich's ataxia 37,67,81,84 .…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 99%